Duodenal polyposis secondary to portal hypertensive duodenopathy - Gurung, Ananta (World J Gastrointest Endosc, 2015)
Portal hypertensive duodenopathy (PHD) is a recognized, but uncommon finding of portal hypertension in cirrhotic patients. Lesions associated with PHD include erythema, erosions, ulcers, telangiectasia, exaggerated villous pattern and duodenal varices. However, duodenal polyposis as a manifestation of PHD is rare. We report a case of a 52-year-old man who underwent esophagogastroduodenoscopy and was found with multiple small duodenal polyps ranging in size from 1-8 mm. Biopsy of the representative polyps revealed polypoid fragments of duodenal mucosa with villiform hyperplasia lined by reactive duodenal/gastric foveolar epithelium and underlying lamina propria showed proliferating ectatic and congested capillaries. The features were diagnostic of polyps arising in the setting of PHD.